Hybrid Sufism for enhancing quality of life: Ethnographic perspective in Indonesia - Suwito, Suwito (HTS teologiese studies, 2022)
Sufism has two main dimensions: vertical (God’s pleasure) and horizontal (harmony with nature, society and local wisdom). In reality, many Sufis are considered less concerned about the balancing between vertical and horizontal dimensions. The research explores the concepts and practices of hybrid Sufism undertaken by Kyais (religious leaders) and their followers in improving quality of life. Ethnography was used for exploring the mindset and activities of Kyai and his followers. This study involved four Kyais in Java and Kalimantan, Indonesia. Research data were obtained through participant observations, in-depth interviews and documentation. The data were analysed by Spadley’s ethnographic steps as follows: (1) domain analysis, (2) taxonomy analysis, (3) componential analysis and (4) cultural-thematic analysis. The results showed that hybrid Sufism could improve quality of life. Hybrid Sufism can better appreciate and interpret local wisdom with an attitude of preserving nature and a positive understanding of worldly wealth, increasing the hard work ethos to achieve material–spiritual qualities.Contribution: This article shows that hybrid Sufism encourages the life of Sufis in harmony between vertical and horizontal aspects. This understanding and lifestyle give rise to respect for others, being friendly to the environment and interpreting life and local wisdom.